Persistence and Diffusion of mecC-Positive CC130 MRSA Isolates in Dairy Farms in Meurthe-et-Moselle County (France) - Bietrix, Jacques; Kolenda, Camille; Sapin, Anaïs; Haenni, Marisa; Madec, Jean-Yves; Bes, Michèle; Dupieux, Céline; Tasse, Jason; Laurent, Fréderic (Frontiers in Microbiology, 2019)
Background. Methicillin resistance in Staphylococcus aureus (MRSA) is classically conferred by the acquisition of the mecA gene encoding an additional penicillin binding protein with low affinity for beta-lactams. A mecA variant, named mecC, was described in 2011. MRSA isolates harboring mecC of both animal and human origin have since been collected in different European countries. In France, animal cases were reported in 4 dairy farms between 2008 and 2013 in the Meurthe-et-Moselle county, all located in a 30 km perimeter, suggesting a possible dissemination of mecC-positive MRSA strains. We performed a prospective study to evaluate the local epidemiology of such strains in terms of i) dissemination among animals, humans and in the environment, and ii) persistence in Meurthe-et-Moselle dairy cattle farms. Methods. The 4 French dairy farms with previous reports of mecC-positive MRSA strains and 14 farms in the same perimeter were included in this study. In each farm, nasal swabs, rectal swabs and milk samples were collected from 10 randomly-selected cows, as well as nasal samples from family pets, volunteer farmers and veterinarians. One farm (E0), in which mecC-MRSA isolates were detected, was selected to study more deeply the dissemination of mecC-positive strains within the farm. After pre-enrichment of swabs and milk, they were subcultured on MSSA/MRSA chromogenic selective agar plates. S. aureus colonies were tested with a multiplex PCR to detect the mecA and mecC genes. The mecC-positive strains were characterized using DNA microarray. Results. mecC-positive strains were recovered in 4 farms, corresponding to the ones with previous reports of mecC-positive MRSA strains, and originated only from dairy cow samples. The screening in the E0 farm showed that 22% of the dairy cows carried mecC-positive MRSA. Three strains were also isolated from the environmental samples. All mecC-positive strains belonged to the clonal complex CC130 and harbored the same spa-type t1736. Conclusion. This study found that mecC-positive MRSA isolates are able to persist within the same farms for several years after being introduced in this setting and are able to widely disseminate but only among dairy cows suggesting that milking machines might be a key player.